A scenario-based approach to evaluating potential environmental impacts following a tidal barrage installation. (November 2015) - Kidd, Ian M.; Fischer, Andrew; Chai, Shuhong; Davis, Jenny A.
Abstract: Total exclusion barrages have a high impact on estuarine systems as they are permanent barriers to tidal flow. The environmental impacts of five putative barrages in various locations within the Tamar River estuary in northern Tasmania, Australia were assessed by considering likely hydrological, morphological and ecological outcomes. We found that all hypothetical barrages would produce downstream silt accretion, some to the point where a major port would become unusable without ongoing dredging. The closer a barrage was located to the mouth of the estuary, the greater the loss of tidal prism, the lower the effect of flushing by floodwaters, and the greater the loss of estuarine biodiversity. Eradication of invasive rice grass ( Spartina anglica ) in the mid estuary is potentially a positive outcome, whilst constant headpond surface heights could cause bank erosion and subsidence. Loss of tidal wetlands would contravene the international treaties protecting the migratory waterbirds which use these habitats. Installation of a barrage at the uppermost location appears to represent the best trade-off between adverse impacts and increased recreational and visual amenity. Unfortunately, barrage installation at any site within the estuary fails to address the major anthropogenic stressors of reduced riverine inflows and tidal flushing. A wider sustainability analysis is needed in which the costs of meeting environmental, social and economic objectives are considered. Highlights: Five putative barrages within Tamar estuary in Tasmania are assessed for morphological, ecological and hydrological impacts. Modelling of morphological impacts shows that detrimental effects increase as the barrage position nears the coast. Similarly ecological and hydrological impacts follow that trend. Findings are supported by evidence from existing barrage installations. Benefits of barrage installation are outweighed by the trade-offs and none of the putative barrages could be recommended.